2022
DOI: 10.3390/antiox11061082
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Oral Exposure to Aflatoxin B1-Induced Renal Dysfunction, Oxidative Stress, and Cell Apoptosis in Mice Kidney by Curcumin

Abstract: Aflatoxin B1 is a contaminant widely found in food and livestock feed, posing a major threat to human and animal health. Recently, much attention from the pharmaceutical and food industries has been focused on curcumin due to its strong antioxidant capacity. However, the therapeutic impacts and potential mechanisms of curcumin on kidney damage caused by AFB1 are still incomplete. In this study, AFB1 triggered renal injury in mice, as reflected by pathological changes and renal dysfunction. AFB1 induced renal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 62 publications
2
53
0
Order By: Relevance
“…Additionally, several clinical studies have shown that curcumin has a strong therapeutic potential for treating a few chronic illnesses, including pulmonary, cancer, neurological, cardiovascular, infectious, neoplastic, psychiatric, and metabolic disorders [ 68 ]. Not surprisingly, several in vitro and animal experimental studies confirmed that curcumin supplementation could offer strong protective effects against AFB1-induced liver injury, mutagenicity, hepatocarcinogenicity, renal dysfunction, ileum damage, immune toxicity via regulating multiple above-mentioned targets [ 26 , 34 , 60 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The detailed molecular pathways are discussed in the section below.…”
Section: Biological Properties Of Curcuminmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, several clinical studies have shown that curcumin has a strong therapeutic potential for treating a few chronic illnesses, including pulmonary, cancer, neurological, cardiovascular, infectious, neoplastic, psychiatric, and metabolic disorders [ 68 ]. Not surprisingly, several in vitro and animal experimental studies confirmed that curcumin supplementation could offer strong protective effects against AFB1-induced liver injury, mutagenicity, hepatocarcinogenicity, renal dysfunction, ileum damage, immune toxicity via regulating multiple above-mentioned targets [ 26 , 34 , 60 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The detailed molecular pathways are discussed in the section below.…”
Section: Biological Properties Of Curcuminmentioning
confidence: 99%
“…Oxidative stress is one of the critical molecular mechanisms of adverse effects caused by many toxic chemical hazards or drugs (e.g., heavy metals, mycotoxins, pesticides, chemotherapy drugs, and antibiotics) [ 88 ]. Multiple studies reported that AFB1 and its derivatives could trigger oxidative stress by inducing the formation of ROS or decreasing intracellular antioxidants or the activities of antioxidant enzymes [ 36 , 70 , 73 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. In the liver tissues, the cytochrome (CYP)1A2 and CYP3A4 could bio-transform into AFBO, which is a harmful and extremely active, electrophilic metabolite.…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...mentioning
confidence: 99%
See 3 more Smart Citations